Male and female reproductives are potential sources of RNA virus dissemination in Solenopsis invicta - Steven M. Valles; Roxie L. White; Quentin D. Read (Journal of Invertebrate Pathology, 2026)

Evaluation of organosilicone surfactants as synergists of Solenopsis invicta virus 3 in Solenopsis invicta - Roxie L. White; Quentin D. Read; Steven M. Valles (Journal of Invertebrate Pathology, 2026)

Wild sources for host plant resistance to Bemisia tabaci in watermelon: insights from behavioral and chemical analyses - Petrina McKenzie-Reynolds; Isiaka A. Owolabi; Anju Biswas; Quentin D. Read; Gaelen R. Burke; Amnon Levi; Alvin M. Simmons (Crop Protection, 2026)

Virome of Solenopsis invicta (Hymenoptera: Formicidae): Intercontinental differences in the native and introduced ranges - Steven M. Valles; Marina S. Ascunce; Quentin D. Read; Roxie L. White; Robert K. Vander Meer (Journal of Invertebrate Pathology, 2025)

The Impact of Disturbance on Tree Size Distributions in the United States - Adam J. Eichenwald; John M. Grady; Jonathan A. Knott; Quentin D. Read; J. Marcos Rodriguez; Sydne Record (Global Ecology and Biogeography, 2025)
Aim Tree size distributions are an emergent feature of forest dynamics across space and time. Theory suggests that undisturbed forests exhibit a size‐abundance distribution captured by a power‐law relationship with a near‐2 slope. We aimed to quantify how disturbances systematically and predictably cause deviations from this expected pattern. Location Contiguous United States. Time Period 2001–2023. Major Taxa Studied Diverse tree communities. Methods We analysed size‐abundance distributions in over 160,000 FIA plots for both disturbed and undisturbed forests, examining changes in slope associated with disturbances, stand age, and maximum tree height. We used a Structural Equation Model (SEM) to evaluate whether disturbance effects on size‐abundance slopes were indirectly mediated by changes in stand age or maximum height. Results We found that the predominant disturbances across the dataset (e.g., ground fires, animal damage) result in predictable flattening of size‐abundance slopes, reflecting the selective removal of smaller trees. In contrast, many disturbances (e.g., wind, disease) did not shift the slopes predictably, indicating that they did not selectively impact any specific size class. Maximum tree height and stand age were also reliable predictors of size‐abundance distributions, but a structural equation model demonstrated that the impact of disturbance on size‐abundance slopes was not mediated through its indirect effects on stand age or maximum tree height, suggesting a direct pathway of influence. Main Conclusions Disturbances result in predictable changes to forest size‐abundance slopes. As climate change and increased disturbance frequencies produce younger and shorter forests, future size‐abundance slopes are expected to be steeper than those in undisturbed forests. Our findings suggest a temporary flattening in the size‐abundance relationship immediately after the predominant disturbances across the dataset (ground fires, animal damage). These findings underscore the importance of understanding disturbance impacts on forest size structure to improve predictions of forests across broad spatial and temporal scales.

Immune responses of chickens against recombinant Salmonella enterica serotype Heidelberg FimA and FimW fimbriae and FliD and FlgK flagellar proteins - Hung-Yueh Yeh; Quentin D. Read (Veterinary Immunology and Immunopathology, 2025)

Interpreting the spatial distribution of soil properties with a physically-based distributed hydrological model - Zamir Libohova; Marcelo Mancini; H. Edwin Winzeler; Quentin D. Read; Ning Sun; Dylan Beaudette; Candiss Williams; Joshua Blackstock; Sérgio H.G. Silva; Nilton Curi; Kabindra Adhikari; Amanda Ashworth; et al. (Geoderma Regional, 2024)

Influence of sample size, model selection, and land use on prediction accuracy of soil properties - Samira Safaee; Zamir Libohova; Eileen J. Kladivko; Andrew Brown; Edwin Winzeler; Quentin Read; Shams Rahmani; Kabindra Adhikari (Geoderma Regional, 2024)

Preliminary assessment of bacterial antibiotic resistance and Candidatus Liberibacter asiaticus titer in three Florida commercial citrus groves - Marie de Gracia Coquerel; Jieli Wegerif; Andrew McAuley; Quentin D. Read; Nabil Chowdhury; Kwang Cheol Jeong; J. Glenn Morris; Samuel J. Martins; Erica M. Goss; Marina S. Ascunce (Crop Protection, 2023)

Corrigendum to: Impact of sweetpotato starch structures, thermal properties, and granules sizes on sweetpotato fry textures [Food Hydrocolloids 137 108377] - Matthew C. Allan; Quentin D. Read; Suzanne D. Johanningsmeier (Food Hydrocolloids, 2023)

Impact of sweetpotato starch structures, thermal properties, and granules sizes on sweetpotato fry textures - Matthew C. Allan; Quentin D. Read; Suzanne D. Johanningsmeier (Food Hydrocolloids, 2023)

Towards mapping biodiversity from above: Can fusing lidar and hyperspectral remote sensing predict taxonomic, functional, and phylogenetic tree diversity in temperate forests? - Aaron G. Kamoske; Kyla M. Dahlin; Quentin D. Read; Sydne Record; Scott C. Stark; Shawn P. Serbin; Phoebe L. Zarnetske (Global Ecology and Biogeography, 2022)
Aim Rapid global change is impacting the diversity of tree species and essential ecosystem functions and services of forests. It is therefore critical to understand and predict how the diversity of tree species is spatially distributed within and among forest biomes. Satellite remote sensing platforms have been used for decades to map forest structure and function but are limited in their capacity to monitor change by their relatively coarse spatial resolution and the complexity of scales at which different dimensions of biodiversity are observed in the field. Recently, airborne remote sensing platforms making use of passive high spectral resolution (i.e., hyperspectral) and active lidar data have been operationalized, providing an opportunity to disentangle how biodiversity patterns vary across space and time from field observations to larger scales. Most studies to date have focused on single sites and/or one sensor type; here we ask how multiple sensor types from the National Ecological Observatory Network’s Airborne Observation Platform (NEON AOP) perform across multiple sites in a single biome at the NEON field plot scale (i.e., 40 m × 40 m). Location Eastern USA. Time period 2017–2018. Taxa studied Trees. Methods With a fusion of hyperspectral and lidar data from the NEON AOP, we assess the ability of high resolution remotely sensed metrics to measure biodiversity variation across eastern US temperate forests. We examine how taxonomic, functional, and phylogenetic measures of alpha diversity vary spatially and assess to what degree remotely sensed metrics correlate with in situ biodiversity metrics. Results Models using estimates of forest function, canopy structure, and topographic diversity performed better than models containing each category alone. Our results show that canopy structural diversity, and not just spectral reflectance, is critical to predicting biodiversity. Main conclusions We found that an approach that jointly leverages spectral properties related to leaf and canopy functional traits and forest health, lidar derived estimates of forest structure, fine‐resolution topographic diversity, and careful consideration of biogeographical differences within and among biomes is needed to accurately map biodiversity variation from above.

Plant removal across an elevational gradient marginally reduces rates, substantially reduces variation in mineralization - Kenna E. Rewcastle; Jeremiah A. Henning; Quentin D. Read; Rebecca E. Irwin; Nathan J. Sanders; Aimée T. Classen (Ecology, 2022)
The loss of aboveground plant diversity alters belowground ecosystem function; yet, the mechanisms underpinning this relationship and the degree to which plant community structure and climate mediate the effects of plant species loss remain unclear. Here, we explored how plant species loss through experimental removal shaped belowground function in ecosystems characterized by different climatic regimes and edaphic properties. We measured plant community composition as well as potential carbon (C) and nitrogen (N) mineralization and microbial extracellular enzyme activity in soils collected from four unique plant removal experiments located along an elevational gradient in Colorado, USA. We found that, regardless of the identity of the removed species or the climate at each site, plant removal decreased the absolute variation in potential N mineralization rates and marginally reduced the magnitude of N mineralization rates. While plant species removal also marginally reduced C mineralization rates, C mineralization, unlike N mineralization, displayed sensitivity to the climatic and edaphic differences among sites, where C mineralization was greatest at the high elevation site that receives the most precipitation annually and contains the largest soil total C pool. Plant removal had little impact on soil enzyme activity. Removal effects were not contingent on the amount of biomass removed annually, and shifts in mineralization rates occurred despite only marginal shifts in plant community structure following plant species removal. Our results present a surprisingly simple and consistent pattern of belowground response to the loss of dominant plant species across an elevational gradient with different climatic and edaphic properties, suggesting a common response of belowground ecosystem function to plant species loss regardless of which plant species are lost or the broader climatic context.

Beyond counts and averages: Relating geodiversity to dimensions of biodiversity - Quentin D. Read; Phoebe L. Zarnetske; Sydne Record; Kyla M. Dahlin; Jennifer K. Costanza; Andrew O. Finley; Keith D. Gaddis; John M. Grady; Martina L. Hobi; Andrew M. Latimer; Sparkle L. Malone; Scott V. Ollinger; et al. (Global Ecology and Biogeography, 2020)
Aim We may be able to buffer biodiversity against the effects of ongoing climate change by prioritizing the protection of habitat with diverse physical features (high geodiversity) associated with ecological and evolutionary mechanisms that maintain high biodiversity. Nonetheless, the relationships between biodiversity and habitat vary with spatial and biological context. In this study, we compare how well habitat geodiversity (spatial variation in abiotic processes and features) and climate explain biodiversity patterns of birds and trees. We also evaluate the consistency of biodiversity–geodiversity relationships across ecoregions. Location Contiguous USA. Time period 2007–2016. Taxa studied Birds and trees. Methods We quantified geodiversity with remotely sensed data and generated biodiversity maps from the Forest Inventory and Analysis and Breeding Bird Survey datasets. We fitted multivariate regressions to alpha, beta and gamma diversity, accounting for spatial autocorrelation among Nature Conservancy ecoregions and relationships among taxonomic, phylogenetic and functional biodiversity. We fitted models including climate alone (temperature and precipitation), geodiversity alone (topography, soil and geology) and climate plus geodiversity. Results A combination of geodiversity and climate predictor variables fitted most forms of bird and tree biodiversity with Main conclusions Although climatic predictors tended to have larger individual effects than geodiversity, adding geodiversity improved climate‐only models of biodiversity. Geodiversity was correlated with biodiversity more consistently than with climate across ecoregions, but models tended to have a poor fit in ecoregions held out of the training dataset. Patterns of geodiversity could help to prioritize conservation efforts within ecoregions. However, we need to understand the underlying mechanisms more fully before we can build models transferable across ecoregions.

Towards connecting biodiversity and geodiversity across scales with satellite remote sensing - Phoebe L. Zarnetske; Quentin D. Read; Sydne Record; Keith D. Gaddis; Stephanie Pau; Martina L. Hobi; Sparkle L. Malone; Jennifer Costanza; Kyla M. Dahlin; Andrew M. Latimer; Adam M. Wilson; John M. Grady; et al. (Global Ecology and Biogeography, 2019)
Issue Geodiversity (i.e., the variation in Earth's abiotic processes and features) has strong effects on biodiversity patterns. However, major gaps remain in our understanding of how relationships between biodiversity and geodiversity vary over space and time. Biodiversity data are globally sparse and concentrated in particular regions. In contrast, many forms of geodiversity can be measured continuously across the globe with satellite remote sensing. Satellite remote sensing directly measures environmental variables with grain sizes as small as tens of metres and can therefore elucidate biodiversity–geodiversity relationships across scales. Evidence We show how one important geodiversity variable, elevation, relates to alpha, beta and gamma taxonomic diversity of trees across spatial scales. We use elevation from NASA's Shuttle Radar Topography Mission (SRTM) and c . 16,000 Forest Inventory and Analysis plots to quantify spatial scaling relationships between biodiversity and geodiversity with generalized linear models (for alpha and gamma diversity) and beta regression (for beta diversity) across five spatial grains ranging from 5 to 100 km. We illustrate different relationships depending on the form of diversity; beta and gamma diversity show the strongest relationship with variation in elevation. Conclusion With the onset of climate change, it is more important than ever to examine geodiversity for its potential to foster biodiversity. Widely available satellite remotely sensed geodiversity data offer an important and expanding suite of measurements for understanding and predicting changes in different forms of biodiversity across scales. Interdisciplinary research teams spanning biodiversity, geoscience and remote sensing are well poised to advance understanding of biodiversity–geodiversity relationships across scales and guide the conservation of nature.

Short-term responses to warming vary between native vs. exotic species and with latitude in an early successional plant community - Kileigh B. Welshofer; Phoebe L. Zarnetske; Nina K. Lany; Quentin D. Read (Oecologia, 2018)

Consistently inconsistent drivers of microbial diversity and abundance at macroecological scales - John Nicholas Hendershot; Quentin D. Read; Jeremiah A. Henning; Nathan J. Sanders; Aimée T. Classen (Ecology, 2017)
Macroecology seeks to understand broad‐scale patterns in the diversity and abundance of organisms, but macroecologists typically study aboveground macroorganisms. Belowground organisms regulate numerous ecosystem functions, yet we lack understanding of what drives their diversity. Here, we examine the controls on belowground diversity along latitudinal and elevational gradients. We performed a global meta‐analysis of 325 soil communities across 20 studies conducted along temperature and soil pH gradients. Belowground taxa, whether bacterial or fungal, observed along a given gradient of temperature or soil pH were equally likely to show a linear increase, linear decrease, humped pattern, trough‐shaped pattern, or no pattern in diversity along the gradient. Land‐use intensity weakly affected the diversity‐temperature relationship, but no other factor did so. Our study highlights disparities among diversity patterns of soil microbial communities. Belowground diversity may be controlled by the associated climatic and historical contexts of particular gradients, by factors not typically measured in community‐level studies, or by processes operating at scales that do not match the temporal and spatial scales under study. Because these organisms are responsible for a suite of key processes, understanding the drivers of their distribution and diversity is fundamental to understanding the functioning of ecosystems.

Consequences of exotic host use: impacts on Lepidoptera and a test of the ecological trap hypothesis - Su’ad Yoon; Quentin Read (Oecologia, 2016)